Comprehensive dataset of interactors for the entire PARP family using TurboID proximity labeling - Jiefu Zheng; Yawen Deng; Cong Fang; Shiyu Xiong; Xudong Zhu; Weijun Wu; Xinliang Chen; Wenjing Wu; Dong Yin; Kaishun Hu; Haiyan Yan (Scientific Data)
Abstract A comprehensive dataset detailing protein interactors for the PARP family has been generated using TurboID proximity labeling under standardized experimental conditions. V5-TurboID fusion constructs enabled identification of 6,314 high-confidence interacting proteins through mass spectrometry, capturing transient interactions undetectable by conventional methods. Parallel GFP-PARP localization experiments validated physiological subcellular distributions. The dataset reveals both shared and unique interactors across PARP members, with network analysis suggesting functional cooperativity and specialization. Functional annotation analyses were performed on representative PARP members to validate key biological processes. All raw proteomic data (PRIDE: PXD052745)29 and processed interaction networks (figshare)50 are publicly available. This comprehensive interactome atlas provides a valuable foundation for advancing our understanding of PARP-mediated regulatory mechanisms and supports therapeutic development.